The Effect of Ramadan on the Indonesian Sharia Stock Index - Husen, Ulfiya; Nasarudin, Indo Yama; Mubarok, Faizul (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2021)
As the most prominent Muslim majority country globally, Ramadan is a viral religious celebration in Indonesia. This study aims to determine the effect of the month of Ramadan on the performance of Islamic stocks in food and beverage companies. This study uses the event study method with a paired sample t-test as a test instrument. Sharia stock performance uses variable returns, abnormal returns, trading volume activity, and variability of securities returns from 2013-2020 during Shaban, Ramadan, and Syawal. This study indicates that the return variable and trading volume activity have a significant difference at the moment and after the month of Ramadan. In contrast, the other tests have no difference. Directly, during the month of Ramadan, the level of public consumption increases along with increasing needs. Indirectly, the traditions of the month of Ramadan also affect performance in the capital market. This phenomenon will affect sentiment in stock transactions based on the festive atmosphere brought by the month of Ramadan.